The demons of modernity : Ingmar Bergman and European cinema - Orr, John, 1943-2010 (Berghahn Books, 2014)
Ingmar Bergman's films had a very broad and rich relationship with the rest of European cinema, contrary to the myth that Bergman was a peripheral figure, culturally and aesthetically isolated from the rest of Europe. This book contends that he should be put at the very center of European film history by chronologically comparing Bergman's relationship to key European directors such as Carl Theodor Dreyer, Jean-Luc Godard, Michelangelo Antonioni, and Andrei Tarkovsky, and also looks at Bergman's critical relationship to key movements in film history such as the French New Wave.